Policy Analysis of Inclusive-Based Education: Case Study of UIN Sunan Kalijaga - Luthfi Nurul Huda, Luthfi; Linda; Muhammad Syihabuddin (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
As we know, education is an essential thing for every nation, one of which is the Indonesian state, because education is an important factor in the progress or retreat of a nation. The more optimal and integrated the education system, the more advanced the nation. According to Sutrisno, in a lecture on the subject of Islamic Education Policy and Leadership in Indonesia, "education is essentially educating, which means not only teaching knowledge to students, but a teacher must be a figure like a parent, namely being an example, guiding, and directing to the path of truth." In carrying out its application, not all students have normal conditions because it is estimated that around 10% of children in the world have special needs. Over time, the number of children with special needs in Indonesia has increased, even though it has not become a constant thing. In reality, the implementation of inclusive-based education policies is still estimated to be less than optimal because there is no policy in an educational institution if there is already an institution that implements the policy but it is still not optimal in its implementation. The key to success in the implementation of inclusive education depends on integration and cooperation between the state, teachers or lecturers, parents, or students. Not a few of the educational institutions at the university level are developing an inclusive education system, but one of the research subjects that the author studied is at UIN Sunan Kalijaga, because inclusive education in the institution is one of the three core values in developing the education system and is a pioneer of inclusive Islamic religious universities.